Automotive Systems Engineering II (Springer International Publishing, 2018)
This book is the second volume reflecting the shift in the design paradigm in automobile industry. It presents contributions to the second and third workshop on Automotive Systems Engineering held in March 2013 and Sept. 2014, respectively. It describes major innovations in the field of driver assistance systems and automated vehicles as well as fundamental changes in the architecture of the vehicles.